2015
DOI: 10.1007/s11096-015-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antithrombotic drug use and adherence to non-vitamin K oral anticoagulants in the Netherlands

Abstract: Background Non-vitamin K oral anticoagulants (NOACs) became available in the Netherlands in 2008, providing another antithrombotic treatment besides vitamin K antagonists (VKAs) and antiplatelet agents (APAs). Objective To describe the patterns of antithrombotic drug use between 2008 and 2013 by examination of dispensing data form community pharmacies in the Netherlands; to determine the concomitant use of NOACs with VKAs and APAs and switching between the drug classes; and to compare adherence to NOACs with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…(iii) Prior stroke, as a dramatic life event, may in itself be an adherence-enhancing factor, as previously suggested [13] . This may explain the lower adherence rates in observational studies in mixed populations [4,[9][10][11][12]16] compared to our study, which included only stroke patients.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…(iii) Prior stroke, as a dramatic life event, may in itself be an adherence-enhancing factor, as previously suggested [13] . This may explain the lower adherence rates in observational studies in mixed populations [4,[9][10][11][12]16] compared to our study, which included only stroke patients.…”
Section: Discussionmentioning
confidence: 71%
“…This is surprising, as adherence in RCTs is criticized as not reflecting real-world situations [1] . In contrast, the vast majority of observational studies have reported lower ≥ 80% adherence rates to NOACs, ranging from 57 to 88% [4,[9][10][11][12] . In turn, there are a few observational studies that reported similarly high rates [8,13] ; the rate of ≥ 80% and full adherence to NOACs was >70 and >90% respectively in one of them [8] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In real-world data, medication adherence level evaluated with proportion of days covered (PDC) method was reported to be in a wide range between 47.7% and 95%. [18][19][20] This discrepancy is thought to result from the difference and number of the population in which medication adherence is assessed, follow-up duration, divergence of indications for NOAC, and diversity of the methods used to evaluate adherence. The studies with self-report method had also controversial results.…”
Section: Adherence To Noacmentioning
confidence: 99%
“…It is a striking finding that data from randomized studies do not align with the real-world data. The studies reflecting the real-world data report a wide range of drug adherence from 47.7% to 95% [19][20][21][22]. The real-world studies have reported different rates of drug adherence due to differences in the study population and study samples, duration of follow-up, different indications for the use of NOAC therapy, and differences in methods to evaluate drug adherence.…”
Section: Discussionmentioning
confidence: 99%